Inaugural Editorial - Rolf Rønning; Anne Marie Berg; Noralv Veggeland; Hans Wiggo Kristiansen; Inger Haug (Nordic Journal of Social Research)
We have the great pleasure to publish the inaugural issue of the Nordic Journal of Social Research. The NJSR is an open-access, net-based journal that publishes peer-reviewed articles shortly after they are accepted following the review process. In this issue, we present three original, peer-reviewed articles. Among these is a contribution from Thomas Scheff of the University of California, Santa Barbara, whose works have had a lasting impact on sociological theory worldwide. Professor Scheff has generously offered us his latest article as a sign of his close cooperation with Nordic scholarship on social research. The other two originate from Sweden, with one by Björn Blom and Lennart Nygren of Umeå University and the other by Carolina Jernbro, Ulla-Britt Eriksson, and Staffan Janson of Karlstad University.